Perancangan Ulang Mesin Penggiling Kedelai Untuk Meningkatkan Hasil Gilingan Kedelai Pada Ukm Tahu Marina - Wahyu Dharma Prasetyo; Anggia Arista (LPPM Universitas Putera Batam, 2018)
Soybean is one type of multipurpose beans because it can be used as raw material formaking food. Nowdays, tofu entrepreneurs especially the scale of SMEs (Small andMedium Enterprises) in Indonesia still using soy grind tool so that the results of soybean mill is insufficient.The grinder of SMEs Tahu Marina where the grinding machine used has a soy container that does not fit the needs of the next process so it requires 2 times the grinding process. To overcome these problems, the authors developed a container soy grinder machine driven by an electric motor. The purpose of this research is to design the container of soy grinder machine in accordance with the needs of the know-making process in SMEs know marina. The result of this research is the design of soybean machine container with capacity 64,5 kg / hour, with height of tube of 52 cm soybean, which is refuted with skeleton which have height 60 cm, length 120 cm, width 60 cm, using electric motor with 3 HP. The capacity of the grinding machine container designed by this author is in accordance with the capacity of the soybean soybean machine container required by SMEs Tahu Marina